2015
DOI: 10.1590/2359-3997000000072
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune central diabetes insipidus in a patient with ureaplasma urealyticum infection and review on new triggers of immune response

Abstract: SUMMARYDiabetes insipidus is a disease in which large volumes of dilute urine (polyuria) are excreted due to vasopressin (AVP) deficiency [central diabetes insipidus (CDI)] or to AVP resistance (nephrogenic diabetes insipidus). In the majority of patients, the occurrence of CDI is related to the destruction or degeneration of neurons of the hypothalamic supraoptic and paraventricular nuclei. The most common and well recognized causes include local inflammatory or autoimmune diseases, vascular disorders, Langer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Furthermore, the patient endorsed her polyuria had remained the same even after GBS diagnosis and treatment, strongly indicating that GBS did not contribute to her CDI. CDI due to inflammatory pathologies is also often characterized by pituitary stalk thickening on T1-weighted MRI [ 20 ], which was not seen on our patient’s MRI ( Figure 1 ). If there were lesions to the posterior pituitary gland from tumors, trauma, or inflammatory pathologies, then there would have also been a disappearance of a bright signal in the posterior pituitary gland on T1-weighted MRI, indicating loss of ADH storage [ 21 ].…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, the patient endorsed her polyuria had remained the same even after GBS diagnosis and treatment, strongly indicating that GBS did not contribute to her CDI. CDI due to inflammatory pathologies is also often characterized by pituitary stalk thickening on T1-weighted MRI [ 20 ], which was not seen on our patient’s MRI ( Figure 1 ). If there were lesions to the posterior pituitary gland from tumors, trauma, or inflammatory pathologies, then there would have also been a disappearance of a bright signal in the posterior pituitary gland on T1-weighted MRI, indicating loss of ADH storage [ 21 ].…”
Section: Discussionmentioning
confidence: 67%
“…CDI is caused by inadequate synthesis/release of AVP, often secondary to surgery or head injury which causes traumatic injury to the hypothalamus or posterior pituitary gland and destruction/degeneration of neurons originating in the supraoptic and paraventricular nuclei of the hypothalamus [3]. The most common and well recognized causes include local inflammatory or autoimmune diseases, vascular disorders, Langerhans cell histiocytosis (LCH), sarcoidosis, tumors such as germinoma/craniopharyngioma or metastases, traumatic brain injuries, intracranial surgery, and midline cerebral and cranial malformations [4]. Rosario et al found that autoimmunity is associated with one third of patients with apparently idiopathic CDI, which should therefore be classified as autoimmune CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Lo más habitual es aislarlo como un patógeno oportunista en pacientes inmunocomprometidos en casos de poliartritis y artritis séptica [ 238 - 241 ]; absceso perifrénico [ 242 ], abscesos cerebrales [ 243 ], osteomielitis [ 244 , 245 ], uretritis [ 246 ], pielonefritis [ 247 ], meningitis postrasplante [ 248 ] e infección periprotésica posquirúrgica [ 249 ]. También asociado a embarazos de riesgo y complicaciones neonatales [ 250 ]; corioamnionitis, enfermedad pélvica inflamatoria, enfermedad pulmonar crónica en pretérminos [ 251 - 253 ], infertilidad [ 254 - 256 ], prostatitis [ 257 ] y vaginosis bacteriana [ 232 ], bronquiolitis en niños [ 258 ], poliartritis séptica en paciente con leucemia linfoblástica aguda [ 259 ], empiema pleural en paciente con linfoma B difuso de célula grande [ 260 ], artritis séptica en paciente con LES [ 261 ], diabetes insípida [ 262 ], bacteriemia postquirúrgica [ 263 ], coinfección junto a Chlamydia trachomatis en el síndrome de Reiter [ 264 , 265 ] y piuria estéril [ 266 ].…”
Section: Especies Implicadas En Patología Humanaunclassified